Touching at a distance: the elaboration of communicative functions from the perspective of the interactants - Héron, Robin; Safin, Stéphane; Baker, Michael; Zhang, Zhuoming; Lecolinet, Eric; Détienne, Françoise (Frontiers in Psychology, 2024)
Touch is an inherent part of human social interactions and the diversity of its functions has been highlighted in numerous works. Given the varied roles of touch, with technology-mediated communication being a big part of our everyday lives, research has been interested in enabling and enhancing distant social interactions with mediated touch over networks. Due to the complexity of the sense of touch and technological limitations, multimodal devices have been developed and investigated. In this article, we explore the use of mediated visual touch in distant social interaction. Adopting an interactionist and collaborative approach to human communication, we focus on the communicative functions of distant touch behaviours which interactants co-elaborate throughout their mediated interactions. For this purpose, we conducted an exploratory study placing five romantically involved couples in interaction, where each discussed shared biographical events via a video call, using mediated touch devices (producing vibration and coloured lights). Their interactions were recorded, and excerpts were presented to participants in interviews using a collective confrontation technique (participants are confronted with a recording of their activity and encouraged to comment on it). This technique allows a better understanding of the participants’ points of view on their use of the touch devices in context. Through analysis of the interviews, our results highlight: (1) a variety of visual-touch functions with a redistribution of functions mostly supported by other modalities of communication in face-to-face interactions, such as illustrating aspects of the ongoing conversation; (2) the visual-touch characteristics as well as the verbal, paraverbal and non-verbal indicators of the interactional context considered by the participants to make sense of the stimuli and; (3) the multifactorial and dynamic aspects of the co-elaboration process of the visual-touch functions, reaffirming the role of interactional context, combined with cultural and biographical knowledge, in the meaning making.